Myanmar Monitoring Platform - Household Surveys : Results from the May 2022 High-Frequency Phone Survey of Households - World Bank (Washington, DC : World Bank, 2022)
This report focuses on the results of round eight high frequency phone survey of households in Myanmar conducted in May 2022.